Happy reunion (Raton, New Mexico Raton Range, 1981)
Newspaper Article on the reunion between Mary Shoemaker and her granddaughter Melba R. Terry.
Master list item #: 10
File location is in the Raton File Cabinet
Keywords: Shoemaker, Mary; Terry, Melba R; Local History; Biography; Life and Customs; Family; Reunions; Raton, New Mexico; Tempe, Arizona; Las Vegas, Nevada